(untitled) (Journal of Engineering, 2014)
This research of using Feldspar in the production self compacting concrete (SCC) ( 5,10,15 )% as partial replacement by weight of cement .In this research some of fresh properties of SCC ( slump flow used V-funnel test and filling ability used ( U- box test ) for concrete mixes and also some of the harden properties of SCC ( compressive and flexural tests ). The research results showed that negative effect of Feldspar on the fresh properties of self compacting concrete but the positive effect of Feldspar on the harden properties of self compacting concrete .